The Use of Panel Data Regression to Identify Students Reading Interest in the Library - Susi Erlinda; Tashid; Ambiyar; Liya Astarilla Dede Warman; Mardainis; Fransiskus Zoromi (JAIA - Journal of Artificial Intelligence and Applications, 2021)
Library visit is an indicator of college academic literacy. The current problem was a decrease on the students’ visit and read at the library of STMIK Amik Riau. Based on the visit data in the library, there was a reduction of the students’ visit for each year, as well as books lent by the students has decreased significantly. The purpose of this study was to identify the correlation between the library facilities and the library services on the students’ reading interest at the library of STMIK Amik Riau by using Panel Data. This study used qualitative and quantitative approach. The population of this study were the visitors at STMIK Amik Riau Library that chosen by using simple random sampling. The data were collected through observation, interviews, questionnaires and documentation. The method used to identify the interest on the students’ to read in the library was Panel Data regression. The procedures of this method were to determine the Panel Data Regression Model Estimation, the selection of Panel Data Regression Model (Estimated Technique) which includes the F Statistical Test (Chow Test), Hausman Test, and Lagrange Multiplier Test. Furthermore, conducted testing the Classical Assumptions (Multicollinearity and Heteroscedasticity) which includes the Multicollinearity test and heteroscedasticity test, followed by a feasibility test (Goodness of Fit) with the F-test hypothesis and Partial t-test. The result of this study showed that there was a correlation between the library facilities and the library services on the students’ reading interest at library of STMIK Amik Riau.